1978
DOI: 10.1103/physrevlett.40.907
|View full text |Cite
|
Sign up to set email alerts
|

Ordered Oxygen Overlayer Associated with Chemisorption State on Al(111)

Abstract: We present experimental evidence of a unique, ordered chemisorption phase in the initial interaction of oxygen with the Al(lll) surface. At high oxygen exposure or high temperature, this phase is shown to transform irreversibly to a bulklike aluminum oxide. The measured temperature dependence, as well as the low-energy electron diffraction, suggests a threefold, centered bonding site. A comparison between calculated and experimental valence-band density of states for the oxygen-covered Al(lll) surface is made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(23 citation statements)
references
References 5 publications
2
21
0
Order By: Relevance
“…This contrasts very much the nonadiabatic kinetics at 300 K. 2 The thermal growth of the (1ϫ1)O ad islands at 350-530 K demonstrates that it is possible to anneal the surface covered with small amounts of O ad without direct, full transformation of the-metastable-chemisorbed oxygen into the thermodynamically stable oxide. This had not been found in previous studies in which, upon annealing, the electronic [12][13][14][15][16] and vibrational spectra 17,18 displayed directly the characteristics of aluminum oxide. This may be explained by the larger exposures ͑30-100 L͒ applied there ͑except in one HREELS study, 17 in which the exposure scale deviates, however, from the other studies also at 300 K 2 ͒.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…This contrasts very much the nonadiabatic kinetics at 300 K. 2 The thermal growth of the (1ϫ1)O ad islands at 350-530 K demonstrates that it is possible to anneal the surface covered with small amounts of O ad without direct, full transformation of the-metastable-chemisorbed oxygen into the thermodynamically stable oxide. This had not been found in previous studies in which, upon annealing, the electronic [12][13][14][15][16] and vibrational spectra 17,18 displayed directly the characteristics of aluminum oxide. This may be explained by the larger exposures ͑30-100 L͒ applied there ͑except in one HREELS study, 17 in which the exposure scale deviates, however, from the other studies also at 300 K 2 ͒.…”
Section: Discussionmentioning
confidence: 51%
“…Using x-ray photoemission spectroscopy ͑XPS͒, the O(1s) peak 12 was found to show similar changes as when the surface was exposed to larger amounts of O 2 Al(2p) state [13][14][15][16] showed a shift by 2.7 eV towards higher binding energy characteristic for the oxide ͑which can be clearly discriminated from the 1.4 eV shifted, chemisorbed state͒, and high-resolution electron energy loss spectroscopy ͑HREELS͒ 17,18 revealed the typical oxidic three peak spectrum. All of these data seem to indicate that upon annealing the chemisorbed oxygen layer just transforms into Al oxide.…”
Section: Introductionmentioning
confidence: 98%
“…A gap of 2.5-3.9 eV between the metal aluminium and oxidised aluminium peaks is generally reported in the literature, whereas lower values (0.5-1.5 eV) are attributed to chemisorbed phases, intermediate oxides or very thin oxide films [11,[23][24][25][26][27][28][29][30][31][32]. Although most of the work in the literature is based on the study of the Al2p peak, Rotole and Sherwood have shown, by comparing a clean aluminium plate and ␣ alumina powder, that the differences between the Al2s and Al ox 2s peaks are very similar to those observed between the Al2p and Al ox 2p peaks [33,34].…”
Section: Oxidation At 925 Kmentioning
confidence: 92%
“…This shift is consistent with the Al ϩ3 state in the ␣ϪAl 2 O 3 . 9 On the other hand the Al 2p binding energy found at 76.4 eV at point O is shifted by 3.2 eV towards higher binding energy with respect to metallic Al. It was proposed that the presence of Cu promotes cracking of the oxide layer or induces an intrinsic loss of electrical resistance in the oxide layer itself.…”
mentioning
confidence: 96%